2023
DOI: 10.1017/s0033291723001204
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal course of endocannabinoids andN-acylethanolamines in hair of mothers and their children in the first year postpartum: investigating the relevance of maternal childhood maltreatment experiences

Abstract: Background Childhood maltreatment (CM) exerts long-lasting psychological and biological alterations in affected individuals and might also affect the endocannabinoid (eCB) system which modulates inflammation and the endocrine stress response. Here, we investigated the eCB system of women with and without CM and their infants using hair samples representing eCB levels accumulated during the last trimester of pregnancy and 10–12 months postpartum. Methods CM exposure was assessed with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 90 publications
16
8
2
Order By: Relevance
“…Speci cally, maternal hair AEA during the third pregnancy trimester was signi cantly lower than at 8 weeks and at two years after birth, partly aligning with ndings by Kumbholz et al 36 who also found an increase from third trimester to nine weeks after birth. 1-AG/2-AG during pregnancy and 8 weeks after birth was signi cantly lower than at 14 months, consistent with prior research nding maternal 1-AG/2-AG increases from pregnancy to 12 months after birth 43 . Finally, PEA levels were higher during pregnancy and eight weeks after birth than at 14 months, which was descriptively also the case in Hitzler et al 43 , albeit not signi cant.…”
Section: Stability Of Parental Hair Ecs/ercs Across the Perinatal Periodsupporting
confidence: 90%
See 4 more Smart Citations
“…Speci cally, maternal hair AEA during the third pregnancy trimester was signi cantly lower than at 8 weeks and at two years after birth, partly aligning with ndings by Kumbholz et al 36 who also found an increase from third trimester to nine weeks after birth. 1-AG/2-AG during pregnancy and 8 weeks after birth was signi cantly lower than at 14 months, consistent with prior research nding maternal 1-AG/2-AG increases from pregnancy to 12 months after birth 43 . Finally, PEA levels were higher during pregnancy and eight weeks after birth than at 14 months, which was descriptively also the case in Hitzler et al 43 , albeit not signi cant.…”
Section: Stability Of Parental Hair Ecs/ercs Across the Perinatal Periodsupporting
confidence: 90%
“…In contrast, 1-AG/2-AG levels were lower at T1, and increased at T4 to a level comparable to women outside the perinatal period 33 . ERC levels at T1 and T3 were comparable to previous research with postpartum mothers 43,48 and were higher than in women outside the perinatal period 33 , but decreased to comparable levels by T4. Fathers' hair AEA and 1-AG/2-AG across all time points were higher than reported outside the perinatal period 9 , whereas hair ERC concentrations were elevated at T1, but decreased to levels similar to outside the perinatal period by T4 9 .…”
Section: Descriptive Classi Cation Of Hair Ec/erc Levels Across the P...supporting
confidence: 81%
See 3 more Smart Citations